Transcript Analysis Reveals a Hypoxic Inflammatory Environment in Human Chronic Otitis Media With Effusion - Bhutta, Mahmood F.; Lambie, Jane; Hobson, Lindsey; Williams, Debbie; Tyrer, Hayley E.; Nicholson, George; Brown, Steve D.M.; Brown, Helen; Piccinelli, Chiara; Devailly, Guillaume; Ramsden, James; Cheeseman, Michael T. (Frontiers in Genetics, 2020)
Chronic otitis media with effusion (COME) is the most common cause of childhood hearing loss in the developed world. Underlying pathophysiology is not well understood, and in particular the factors that lead to the transition from acute to chronic inflammation. Here we present the first genome-wide transcript analysis of white blood cells in the effusion of children with COME. Analysis of microarray data for enriched pathways reveals upregulation of hypoxia pathways, which is confirmed using real-time PCR and determining VEGF protein titres. Other pathways upregulated in both mucoid and serous effusions include Toll-like receptor signalling, complement, and RANK-RANKL. Cytology reveals neutrophils and macrophages predominated in both serous and mucoid effusions, however, serous samples had higher lymphocyte and eosinophil differential counts, while mucoid samples had higher neutrophil differential counts. Transcript analysis indicates serous fluids have CD4+ and CD8+ T-lymphocyte, and NK cell signatures. Overall, our findings suggest that inflammation and hypoxia pathways are important in the pathology of COME and targets for potential therapeutic intervention, and that mucoid and serous COME may represent different immunological responses.